Requirement analysis approach for Universiti Utara Malaysia (UUM) Library Data Warehouse - Ta'a, Azman (2012)
Requirements play a very important role in software development and forms as a backbone of any successful or failure of the IT project. Careless of requirements interpretation would increase cost and hinder the system development to satisfy user’s expectation. Therefore, it is necessary to present the requirement in an understandable and meaningful way.This is achieved through a proper requirement process, which gives a complete view of data warehouse (DW) system and represents idea without having to explore into an actual system.This research aims to propose a requirement analysis approach for UUM Library DW system. Snowflake dimension model is used to present the DW structure that derived from a set of requirement lists, which was produced from the requirement analysis process.Various reports were designed and validated by the authorized librarian. Several limitations were discussed, and recommendations for future research were suggested.